DDEL-13. ULTRASOUND-ENHANCED DELIVERY OF LIPOSOMAL DOXORUBICIN ACROSS THE BLOOD BRAIN BARRIER INDUCES AN IFN-GPHENOTYPE IN MICROGLIA, MACROPHAGES, AND T CELLS AND IMPROVES RESPONSE TO PD-1 BLOCKADE IN GLIOMAS. (14th November 2022) - Arrieta, Victor; Gould, Andrew; Kim, Kwang Soo; Dmello, Crismita; Zhang, Daniel; Castro, Brandyn; Chen, Li; Pandey, Surya; Kai, Li; Duffy, Joseph; McCord, Matthew; Ward, Rachel; et al.
Abstract: INTRODUCTION: Given the limited drug penetration across the blood-brain barrier (BBB), the therapeutic potential of new and existing therapies has not been fully exploited for the benefit of glioblastoma (GBM) patients. METHODS: Here we employed a novel drug delivery technology based on low-intensity pulsed ultrasound combined with intravenous microbubbles (LIPU/MB) that temporarily opens the BBB to deliver liposomal doxorubicin (DOX) and anti-PD-1 therapy (aPD-1) in mouse glioma models and 3 recurrent GBM patients. Immunological variables were evaluated in tumor and immune cells as well as efficacy in glioma-bearing mice treated with DOX delivered by LIPU. These included measurement of HLA ABC and HLA DR protein expression by tumor cells, microglia, and macrophages and IFN-g production by glioma-associated microglia and macrophages in mouse and human tumors. We also assessed efficacy of LIPU/MB enhanced combination therapy in glioma-bearing mice. RESULTS: Upregulation of HLA ABC and HLA DR was observed in GBM cell lines at low concentrations of DOX. Tumor cells from GBM patients treated with DOX, aPD-1 and LIPU/MB showed increased expression of HLA ABC and HLA DR compared to paired pretreatment samples. In both mice and humans, LIPU/MB liposomal DOX increased absolute brain drug concentrations and elicited a specific IFN-g phenotype and MHC I expression in glioma-associated microglia and macrophages in mice and humans. Furthermore, LIPU/MB-mediated BBB opening increased brain concentrations of aPD-1 in mice and in peritumoral regions of GBM patients. Combined treatment with liposomal DOX and aPD-1 delivered with LIPU/MB resulted in long-term survival of glioma-bearing mice that relied on the activity of CD8 + T cells for its efficacy. CONCLUSIONS: Overall, this translational study demonstrates the utility of LIPU/MB to stimulate intracranial immune responses in the context of treatment with DOX and aPD-1 for gliomas.